PENGEMBANGAN BAHAN AJAR PERTIDAKSAMAAN LINEAR SATU VARIABEL BERBASIS PMRI LEVEL HOTS DI SMP - Titin Riyanti (ELIPS: Jurnal Pendidikan Matematika, 2022)
This study aims to find teaching materials based on single variable linear inequality PMRI level HOTS valid and practical. Research method consists preliminary and prototyping that includes self evaluation, expert review, one to one, small group and field test. Data collection techniques are walk trough, documentation, interviews and questionnaires. The data collected was analyzed qualitatively. The results of data analysis concluded that the teaching materials have a valid and practical. Valid seen from (1) in terms of content, according to the 2013 curriculum, content and context to understand; (2) The terms construct, according to characteristics and principles PMRI and there are indicators HOTS; (3) In terms of language, in accordance with the EYD. For practical seen from (1) in terms of efficient, easy to use teaching materials; (2) In terms of usability, the problem to help students understand material; (3) In terms of the attractiveness, interesting problems to be studied.